Comparison of the diagnostic efficiency of various noninvasive methods for diagnosing liver fibrosis in patients with chronic viral hepatitis C - Moroz, L. V.; Bondaruk, I. Yu.; Popovich, A. A.; Kulias, S. N. (Journal of Education, Health and Sport, 2019)
Summary: the article presents the results of the examination of patients with chronic viral hepatitis C namely the study of the informativeness of instrumental (fibroelastography) and serological (the content of hyaluronic acid in serum) of markers of fibrosis by assessing their predictive value by ROC- analysis. The purpose of the study: to find out the possibility of non-invasive methods for diagnosing liver fibrosis in patients with chronic viral hepatitis C (CHC). Materials and methods 66 patients with CHC with the 1-st genotype of the virus were examined, which were at the dispensary observation and ambulatory treatment at DCC CCH №1 in Vinnitsa and in the clinical department of viral hepatitis at the Institute of Epidemiology and Infectious Diseases named after L.V. Gromashevsky NAMS of Ukraine. All patients received fibroelastography (FEG) with a METAVIR score. All patients with CHC and group of control determined the content of hyaluronic acid (GA) in blood serum (ELISA using the Hyaluronic Acid (Corgenix, Inc., USA)). Research results Sensitivity of determination of GA in blood serum of patients with CHC with degree of fibrosis of liver F0-F2 was 91.23%, and specificity - 90.46%. For the FEG method, respectively: 74.33% and 77.25%. In the group of patients with degree of fibrosis F3 sensitivity of the definition of GA in blood serum was 72.21%, and specificity - 74.71%. The corresponding qualitative characteristics for FEG were: 98.32% and 91.45% respectively. The sensitivity of the determination of the content of GA in serum of patients with CHC with the degree of liver fibrosis F4 was 88.23%, and the specificity was 92.12%. For these patients the sensitivity and specificity of determining the degree of fibrosis by the FEG method were 87.78% and 91.45% respectively. Conclusions High diagnostic efficiency of determination of the content of GA in serum was established for assessing the degree of liver fibrosis in patients with CSF (AUC = 0,720-0,917, p˂0,01). Relatively higher sensitivity and specificity of the diagnosis of liver fibrosis was observed in determining the content of GA in serum compared with the FEG method (AUC = 0.914 vs. AUC = 0.817 (p˂0.05)) in the group with a lack or initial signs of liver fibrosis (F0-F2).